PERENCANAAN REKAM MEDIS BERDASARKAN UNSUR MANAJEMEN DI SUNGAI SIRAI KESEHATAN MASYARAKAT KUANTAN KABUPATEN SINGINGI TAHUN 2018 - Nunung Anjarwati, Sy.Effi Daniati, (Menara Ilmu, 2019)
Planning (human resources planning) is planning work force effectively and efficiently tomeet the needs of companies in helping the realization of the goals and the planning isdone by setting the program staffing, planning in public health will be achieved when thereis an element of an’s management, Money, Material, Machine, Method. Sungai SirihPublic Health Planning have not been implemented optimally. The registration does notuse queue number, registration in the betel river health centers are still manual, and theabsence of an educated Planning based on elements of Management in Sungai Sirih publichealth district Kuantan Singingi Year 2018.This research is descriptive research usingother types of qualitative research, carried out in April in the betel river health centers.Informant this research amounted to 3 people. The technique of data collection byobsevation and interviews, data processing using triangulation, while qualitative analysisused analisi.Of research results, based on elements of Man had a medical record officersare set to high school education and medical ricord all tasks concurrently, based onelements of Money Heads of clinics have never make the budget for the medical record,based on the material elements are readily available if needed. Based on the elementsbased on SOP the Registration, storage, reporting.Planning based on elements of the Manhas not been in accordance with the Health Human resource Planning. Based on theelement of Money does not yet have the budget to use the computer, based on the elementsof the Material is readily available if need. Based on the elements of the Machine has notbeen implementation of registration use a computer, based on the Methode of the elementdoes not have an SOP in registration and storage.Keyword: Medical Record, Planning The Elements Of Management